Late postpartum depression and associated factors: community-based cross-sectional study - Lema Fikadu Wedajo; Solomon Seyife Alemu; Mohammedamin Hajure Jarso; Aman Mamo Golge; Dejene Edosa Dirirsa (BMC, 2023)
Abstract Background Late postpartum depression is the presence of depressive symptoms beyond the early postpartum period and is a significant mental health problem that has a devastating impact on mothers, infants, partners, family members, the healthcare system, and the world's economy. However, there is limited information regarding this problem in Ethiopia. Objective To assess the prevalence of late postpartum depression and associated factors. Method the community-based cross-sectional study was employed among 479 postpartum mothers in Arba Minch town from May 21 to June 21, 2022. The pre-tested face-to-face interviewer administered a structured questionnaire used to collect the data. A bivariate and multivariable analysis was done using a binary logistic regression model to identify factors associated with late postpartum depression. Both crude and adjusted odds ratios with 95% CI were calculated, and a p-value of < 0.05 was used to declare statistically significant factors. Result The prevalence of late postpartum depression was 22.98% (95% CI: 19.16, 26.80). Husband Khat use (AOR = 2.64; 95% CI: 1.18, 5.91), partner dissatisfaction with the gender of the baby (AOR = 2.53; 95% CI: 1.22, 5.24), short inter-delivery interval (AOR = 6.80; 95% CI: 3.34, 13.84), difficulty to meet husband sexual need (AOR = 3.21; 95% CI: 1.62, 6.37), postpartum intimate partner violence (AOR = 4.08; 95% CI: 1.95, 8.54), and low social support (AOR = 2.50; 95% CI: 1.25, 4.50) were significantly associated factors at p-value < 0.05. Conclusion Overall, 22.98% of mothers suffered from late postpartum depression. Therefore, based on the identified factors, the Ministry of Health, Zonal Health Departments, and other responsible agencies should establish effective strategies to overcome this problem.